An Analysis Of Smoking Policy Attitudes Of Low- Income Group And Cigarette Consumption Patterns Upon Increased Wage - Mustafa Atahan Yılmaz; Onur Kulaç (European Scientific Journal, ESJ, 2016)
As one of the most threatening issues in human life, smoking has been faced with many public policies in developed and developing countries. Even health issues which are caused by smoking are overwhelmingly known by the communities, smoking keeps its significance by damaging the health and budget which are directly connected with the life quality. Low-income groups who usually work for the minimum wage are one of the most affected parts of the population. Minimum wage has been increased about 30% in Turkey in the last quarter of 2015. This study generally aims to reveal cigarette purchase behaviour of low-income groups in Turkey after the salary increase which is highly critical in the context of purchasing power. Moreover in this paper, the perception of low-income groups to public education and restrictions on smoking public policies will be scrutinized.